Overview on the characteristics of houseboats in the Royal Belum State Park, Perak, Malaysia - Rohaslinda Ramele Ramli; Norashikin Ahmad Kamal (Journal of Asian Architecture and Building Engineering)
In Royal Belum State Park, Perak, Malaysia, houseboats have become tourist attractions, complementing its biodiversity and natural landscape. Nevertheless, studies have yet to be carried out on houseboats in Malaysia in general or in Royal Belum State Park, indicating a lack of concern about protecting the sustainability of houseboat tourism. Therefore, this study aims to reveal the characteristics of houseboats in Malaysia, represented by houseboats in the Royal Belum State Park. The study’s objectives are to identify the history of houseboat operation in Royal Belum State Park, regulations on houseboats and operators, houseboat operation and management, houseboats’ design and construction, and issues and challenges the houseboat operators face. This study employs a comprehensive methodology, including literature reviews of research publications and official portals and analysis of reports and statistics from the Pulau Banding Jetty. Interviews with houseboat owners and operators provide insights into houseboat management’s history, operation, and challenges. Detailed field investigations focus on houseboat types, tourism activities, and design characteristics. Measurements and drawings clarify the spatial usage and structural details of the houseboats. The study’s findings will help Malaysia recognize houseboats as official tourist accommodations and work toward achieving Sustainable Development Goals (SDG9)